Conduction disorders using the Evolut R prosthesis compared with the CoreValve: has anything changed?. Issue 1 (25th March 2018) - Perrin, Nils; Perrin, Tilman; Hachulla, Anne-Lise; Frei, Angela; Müller, Hajo; Roffi, Marco; Cikirikcioglu, Mustafa; Ellenberger, Christoph; Licker, Marc-Joseph; Burri, Haran; Noble, Stephane
Abstract : Aim: We compared early postprocedural and midterm evolution of atrioventricular and intraventricular conduction disorders following implantation of the new generation Evolut R (ER) prosthesis in comparison with the previous generation CoreValve (CV) system using routinely recorded ECG up to 6-month follow-up. Methods: All consecutive patients treated by transcathether aortic valve implantation (TAVI) using the Medtronic self-expanding devices for symptomatic severe aortic stenosis in a single centre between October 2011 and February 2016 were considered for inclusion. ECGs recorded at baseline, day 1 after TAVI, discharge and 6 months were retrospectively analysed. At each time-point, intrinsic rhythm, PR interval, QRS axis and duration, and atrioventricular and intraventricular conduction were analysed. Atrioventricular and intraventricular conduction following TAVI at discharge and at 6 months were compared intrasubject at the different time intervals and between patients receiving the ER versus the CV prosthesis. Results: Among the 113 patients included in the analysis (51% female, 83.3±6.2 years), 60 (53%) patients received the CV and 53 (47%) patients received the ER. Compared with patients in the CV group, those in the ER group had a lower Society of Thoracic Surgeons score (6.3±3.1vs 4.8±3.6, P=0.02). Patients in the ER group in comparison with those in the CV group more frequently had postprocedural PR interval (57%vs23%, respectively, P=0.004) and QRS prolongation (76%vs50%, P=0.03) at discharge. Incidence of complete atrioventricular block was similar between both groups (9%vs18%, P=0.3) up to 6-month follow-up. No difference in term of new left bundle branch block (LBBB) (34%vs28%, P=0.8) or permanent pacemaker implantation rates (32.1%vs31.7%, P=1.0) was reported. Conclusions: Patients with the ER had greater postprocedural atrioventricular and intraventricular conduction delays than those with the CV at discharge, with however similar incidence of high-degree atrioventricular block, new LBBB and permanent pacemaker implantation up to 6-month follow-up.